The frequency-following response in late preterm neonates: a pilot study - Ribas-Prats, Teresa; Arenillas-Alcón, Sonia; Martínez, Silvia Irene Ferrero; Gómez-Roig, Maria Dolores; Escera, Carles (Frontiers in Psychology, 2024)
Infants born very early preterm are at high risk of language delays. However, less is known about the consequences of late prematurity. Hence, the aim of the present study is to characterize the neural encoding of speech sounds in late preterm neonates in comparison with those born at term. The speech-evoked frequency-following response (FFR) was recorded to a consonant-vowel stimulus /da/ in 36 neonates in three different groups: twelve preterm neonates (mean gestational age [GA] 36.05 weeks), 12 "early term neonates" (mean GA 38.3 weeks), and "late term neonates" (mean GA 41.01 weeks).From the FFR recordings, a delayed neural response and a weaker stimulus F0 encoding in premature neonates compared to neonates born at term was observed. No differences in the response time onset nor in stimulus F0 encoding were observed between the two groups of neonates born at term. No differences between the three groups were observed in the neural encoding of the stimulus temporal fine structure. These results highlight alterations in the neural encoding of speech sounds related to prematurity, which were present for the stimulus F0 but not for its temporal fine structure.